A revision of the Australian endemic water beetle genus Gymnanthelius Perkins (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2004)
The Australian endemic water beetle genus Gymnanthelius Perkins is revised, based on the study of 1,995 specimens. Five new species are described: G. lamingtonensis (Queensland, Lamington, Binna Burra), G. maxipunctus (New South Wales), G. opacicollis (Victoria, Traralgon Creek., 0.2 km N. “Hogg Bridge”, 5.0 km NNW Balook), G. porchi (Victoria, Possum Hollow Falls, W. br. Tarwin River, 5.6 km SSW Allambee), and G. tunicus (Victoria, Traralgon Creek., 0.2 km N. “Hogg Bridge”, 5.0 km NNW Balook). A key to the eight known species is given. High resolution digital images of all holotypes are presented (online version in color), geographic distributions are mapped, and the male genitalia are illustrated. Available microhabitat data indicate that Gymnanthelius species prefer cooler climates, either at lower elevations in southern latitudes or higher elevations in more northern latitudes; southern species are usually found in muddy/silty substrates, whereas more northern species are typically found in sandy/gravelly substrates.